A Systematic Literature Review on Enterprise Risk Management: Trends, Gaps, and Future Directions - Hasanah, Ulfanianatul; Rodiah, Siti; Jannah, Siti Ifa Nur (Economic: Journal Economic and Business, 2025)
This study presents a systematic literature review of Enterprise Risk Management (ERM), focusing on prevailing trends, methodological patterns, research gaps, and future directions over the past five years. Using a qualitative approach, the research analyzes peer-reviewed academic publications and organizational documents, particularly within the Indonesian context. The review reveals that while ERM is increasingly recognized as a strategic necessity in managing multidimensional risks, its implementation remains fragmented and often symbolic rather than substantive. Key findings highlight limited theoretical integration, a lack of longitudinal studies, and minimal exploration in developing economies. Observational data further demonstrate that ERM in Indonesian organizations is often compliance-driven and disconnected from strategic decision-making. Document analysis also reveals a gap between formal policies and practical execution, underscoring the need for improved institutional support, risk literacy, and leadership commitment. This study concludes that a paradigm shift toward value-driven, technology-enabled, and sustainability-oriented ERM is essential. The review provides a conceptual foundation for harmonizing theory and practice and offers actionable insights for future research and policy.